Intrapersonal and Interpersonal Range of Student Skills in Mathematics Learning - Hidayati, Wiwin Sri; Tristanti, Lia Budi (FKIP Universitas Lampung, 2024)
The aim of the research is to determine and create levels of intrapersonal and interpersonal skills in mathematics learning. This research includes qualitative research, the research subjects are MTsN 9 Jombang students. The main instrument is the researcher, supporting instruments: observation guide and interview guide. The research results found 3 levels of intrapersonal and interpersonal skills, namely high, medium and low. There are 3 levels, namely a high level of intrapersonal skills and a high level of interpersonal skills, 14 students, a medium level of intrapersonal skills and a moderate level of interpersonal skills, 5 students, a medium level of intrapersonal skills and low interpersonal skills, 13 students. Students who have a high level of intrapersonal skills and a high level of interpersonal skills are leaders or active social actors among their classmates. Students who are at a moderate level of intrapersonal skills and moderate levels of interpersonal skills are students who show a combination of characteristics and reflect a balanced ability to understand themselves and interact with others. Students with moderate levels of intrapersonal skills and low levels of interpersonal skills are students who have difficulty communicating effectively with others, lack self-confidence, are unsure in social interactions, have difficulty working together in groups, have difficulty understanding and adapting to social dynamics, tend to prefer to work alone or have their own time, and are less active in discussions. Keywords: intrapersonal, interpersonal, mathematics learning DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp166-177